Predictors of Concomitant Coronary Artery Disease and Major Cardiovascular Events in Patients with Acute Ischemic Stroke - ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (Wolters Kluwer Medknow Publications, 2021)
Background: Coronary artery disease (CAD) and ischemic stroke share the same risk factors. Objective: The aim of the study was to explore the prevalence and predictors of concomitant CAD in acute ischemic stroke patients. Methods: One hundred and five patients (64.3 ± 15.0 years, 61 male) presenting with acute ischemic stroke documented by neuroimaging were consecutively included. All patients were carefully evaluated to determine their cardiovascular disease risk scores. The patients who had been previously shown to have ≥50% stenosis in at least one of the major coronary arteries by coronary angiography were grouped as CAD patients. Results: Of the 105 stroke patients, 27 patients had documented concomitant CAD. The stroke patients with CAD had higher cardiovascular risk scores and troponin I levels and carotid plaques were more prevalent. ROC analysis determined cut-off values as ≥22% for Framingham Heart Study Risk Score, ≥0.05 ng/mL for Troponin I, and ≥0.80 mm for carotid artery intima-media thickness to predict concomitant CAD. During 6 months of follow-up, among the 78 stroke patients without documented CAD, 16 patients had experienced major cardiovascular events including myocardial infarction, recurrent stroke, or cardiovascular death. These patients had higher Framingham Heart Study Risk Score and high-sensitive C reactive protein levels. Conclusion: Our study suggests stroke patients with higher Framingham Heart Study Risk Score and troponin I levels and carotid plaques be further investigated for the presence of concomitant CAD. © 2021 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Acute ischemic stroke; carotid intima-media thickness; coronary artery disease; Framingham Heart Study Risk Score; troponin I